Penerapan Metode Pijat Refleksi Kaki pada Lansia Penderita Hipertensi di Desa Palur Kabupaten Sukoharjo - Khaulah Rafiqoh Kamelani; Eska Dwi Prijayanti (PPNI UNIMMAN, 2024)
Background: Elderly is an aging process with increasing age which is characterized by a decrease in the ability of organ functions and an increase in the loss of active tissue, which makes the body more susceptible to various types of diseases. One of the diseases that elderly people often suffer from is hypertension or high blood pressure. One non-pharmacological treatment that can be done is the foot reflexology massage method..Purpose: To describe the results of comparing blood pressure before and after applying the foot reflexology massage method to elderly hypertensive people. Method: his study used a descriptive design on 2 elderly respondents with hypertension, which was carried out 3x a week with a frequency of 1x a day for 15-20 minutes. Results: There was a decrease in blood pressure after applying the foot reflexology massage method to Mrs. Y went from stage I hypertension to still being in the stage I hypertension category but has experienced a decline and Mrs. S from stage II hypertension to stage I hypertension.. Conclusion: Application of the foot reflexology massage method can reduce blood pressure in elderly people with hypertension.